Legal issues of animal protection in the State of Florida (Journal of actual problems of jurisprudence, 2023)
Animal rights protection has become an increasingly important and relevant topic. In this article we’ll look at legal considerations regarding animal welfare in Florida, USA. With its abundance of biodiversity and ecosystem resources, Florida provides an ideal place for developing legislation ensuring animal wellbeing. This study will aim to analyze the fundamental principles and concepts underlying Florida’s legal system for animal protection. We will explore laws which determine animal rights and responsibilities, such as those intended to safeguard wildlife or prevent cruelty against them. This research pays special consideration to its scientific and practical ramifications, helping better understand legal protection for animals, raise public awareness of this topic, implement laws that enhance animal living conditions and shape public awareness campaigns. Methodologies included an examination of Florida legislation, court rulings and non-profit animal protection organizations. These study’s key findings allow us to establish the need for legislation protecting animal rights as well as Florida’s continued development and strengthening of its animal protection system. This study is vitally important, as it allows us to bring to light an important topic and legal issues relating to animal protection. It will benefit legislators and stakeholders alike while contributing to legal mechanisms protecting animals not just in Florida but worldwide. Key words: animals, animal rights, cruel treatment, animal cruelty.